Cadmium Contamination in Soil and Water and Its Impact on Human Health in Southeast Asia: A Systematic Review - Yulia Khairina Ashar; Andhara Tisya; Diva Keysha Aura Silalahi; Naila Nafisah; Dita Sajidah Poerwansyah (GLOBAL HEALTH SCIENCE GROUP, 2026)
This Cadmium (Cd) is a highly toxic heavy metal that poses serious threats to environmental and human health, especially in Southeast Asia, where industrial, mining, and agricultural activities are rapidly increasing. Chronic exposure to cadmium can lead to kidney damage, bone disorders, reproductive issues, and cancer, especially in areas relying on local water and food sources. This study employed a systematic literature review method, analyzing relevant studies published from databases including PubMed, Scopus, Google Scholar, and ScienceDirect. Keywords used included